Cities, Culture, Creativity : Leveraging Culture and Creativity for Sustainable Urban Development and Inclusive Growth - UNESCO; World Bank (Paris: UNESCO, and Washington, D.C.: World Bank, 2021)
Culture and creativity have untapped potential to deliver social, economic, and spatial benefits for cities and communities. Cultural and creative industries are key drivers of the creative economy and represent important sources of employment, economic growth, and innovation, thus contributing to city competitiveness and sustainability. Through their contribution to urban regeneration and sustainable urban development, cultural and creative industries make cities more attractive places for people to live in and for economic activity to develop. Culture and creativity also contribute to social cohesion at the neighborhood level, enable creative networks to form and advance innovation and growth, and create opportunities for those who are often socially and economically excluded. The ongoing COVID-19 pandemic has had a deep impact on the cultural sector, yet it has also revealed the power of cultural and creative industries as a resource for city recovery and resilience. More generally, cities are hubs of the creative economy and have a critical role to play in harnessing the transformative potential of cultural and creative industries through policies and enabling environments at the local level. ‘Cities, Culture, and Creativity’ (CCC) provides guiding principles and a CCC Framework, developed by UNESCO and the World Bank, to support cities in unlocking the power of cultural and creative industries for sustainable urban development, city competitiveness, and social inclusion. Drawing from global studies and the experiences of nine diverse cities from across the world, the CCC Framework offers concrete guidance for the range of actors — city, state, and national governments; creative industry and related private-sector organizations; creatives; culture professionals and civil society— to harness culture and creativity with a view to boosting their local creative economies and building resilient, inclusive, and dynamic cities.